Chitogel improves long-term health economic outcomes following endoscopic sinus surgery in severe chronic rhinosinusitis patients - Barber, Jacqueline M.; Bouras, George; Robinson, Grace S.; Robinson, Simon R. (Frontiers in Health Services, 2024)
Introduction: Chronic rhinosinusitis causes severe symptoms that can affect patient quality of life. Endoscopic sinus surgery can be effective in improving symptoms, although surgical outcomes can be compromised post-operatively, and revision surgery is required in a proportion of patients. This study compares outcomes and healthcare resource use in patients undergoing sinus surgery with or without Chitogel as a post-operative dressing.Methods: A retrospective cohort study was conducted using deidentified audit data from adult patients with severe chronic rhinosinusitis, who underwent endoscopic sinus surgery between January 2016 and December 2021. Patients in the intervention group received Chitogel as a postoperative dressing, and control patients received standard best-practice care. Cox Proportional Hazards survival analysis was used to compare revision surgery rates and time to revision between treatment groups. The rate of revision surgery was used to estimate potential health sector savings associated with use of Chitogel following surgery compared to the control arm, considering initial treatment costs and the cost of revision surgery.Results: Over 18-24 months, patients treated with Chitogel demonstrated significantly lower rates of revision surgery (p = 0.035), and a trend towards decreased use of post-operative steroids, compared to control. Potential health sector savings due to reduced rates of revision surgery following use of Chitogel are estimated as NZ $753,000 per 100 patients.Severe chronic rhinosinusitis patients treated with Chitogel had lower rates of revision surgery within the first 18-24 months post-operative. These findings suggest that use of Chitogel can improve long-term patient outcomes and should improve health system efficiency.